2010
DOI: 10.1105/tpc.110.074591
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisRETINOBLASTOMA-RELATED Is Required for Stem Cell Maintenance, Cell Differentiation, and Lateral Organ Production  

Abstract: Several genes involved in the regulation of postembryonic organ initiation and growth have been identified. However, it remains largely unclear how developmental cues connect to the cell cycle. RETINOBLASTOMA RELATED (RBR) is a plant homolog of the tumor suppressor Retinoblastoma (pRb), which is a key regulator of the cell cycle. Using inducible RNA interference (RNAi) against Arabidopsis thaliana RBR (RBRi), we reduced RBR expression levels at different stages of plant development. Conditional reduction or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
172
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(183 citation statements)
references
References 125 publications
7
172
1
Order By: Relevance
“…Similar approaches in Arabidopsis and tobacco confirmed that several promotive cell cycle components, such as cyclins CYCD3 or CYCD6, are downregulated in response to ABP1 knock-down and with corresponding phenotypes (Braun et al, 2008;Tromas et al, 2009). ABP1 downregulation also led to an increase in RETINOBLASTOMA RELATED (RBR) expression, which negatively affects cell division and has recently been related to cell differentiation (Borghi et al, 2010). Overexpression of CYCD3;1 or downregulation of RBR in ABP1 knock-down plants partially restored the cell proliferation defects (Tromas et al, 2009), indicating that downregulation of ABP1 affects the cell cycle via the CYCD/RBR pathway.…”
Section: Cell Cyclementioning
confidence: 99%
“…Similar approaches in Arabidopsis and tobacco confirmed that several promotive cell cycle components, such as cyclins CYCD3 or CYCD6, are downregulated in response to ABP1 knock-down and with corresponding phenotypes (Braun et al, 2008;Tromas et al, 2009). ABP1 downregulation also led to an increase in RETINOBLASTOMA RELATED (RBR) expression, which negatively affects cell division and has recently been related to cell differentiation (Borghi et al, 2010). Overexpression of CYCD3;1 or downregulation of RBR in ABP1 knock-down plants partially restored the cell proliferation defects (Tromas et al, 2009), indicating that downregulation of ABP1 affects the cell cycle via the CYCD/RBR pathway.…”
Section: Cell Cyclementioning
confidence: 99%
“…Subsequently, E2F/DP-dependent transcription of cell cycle genes promotes S phase entry and cell cycle progression. Because of its central role in controlling the transcription of cell cycle genes, RB serves as a convergence point for regulating the cell cycle in response to internal and external mitogenic signals (Nakagami et al, 2002;Stevaux et al, 2002;Cobrinik, 2005;Dimova and Dyson, 2005;Wikenheiser-Brokamp, 2006;Jullien et al, 2008;van den Heuvel and Dyson, 2008;Borghi et al, 2010;Henriques et al, 2010;Johnston et al, 2010;Chen et al, 2011;Gutzat et al, 2011Gutzat et al, , 2012Weimer et al, 2012). Recent studies also provide evidence that RB depletion causes metabolic reprogramming and suggest that the RB pathway in animals exerts part of its effect on cell proliferation through the control of Gln metabolism (Nicolay et al, 2013;Reynolds et al, 2014).…”
mentioning
confidence: 97%
“…This coordination appears to depend at least in part on certain cell cycle regulators themselves. For example, in Arabidopsis thaliana, reduction of RBR expression levels in the shoot meristem caused diminished expression of CLAVATA3 and WUSCHEL regulating stem cell identity (Borghi et al, 2010). Similarly, the induction of a kinase-negative form of CDKA in the shoot meristem caused a portion of the meristem cells to expand and exhibit endoreduplication and thus resemble differentiated cells (Gaamouche et al, 2010).…”
Section: Introductionmentioning
confidence: 99%